The Poetry of Prompts: The Collaborative Role of Generative Artificial Intelligence in the Creation of Poetry and the Anxiety of Machine Influence (Global Journal of Computer Science and Technology, 2023)
2022 has been heralded as the year of generative artificial intelligence AI Generative AI like ChatGPT and Stable Diffusion along with a host of others launched late in the year and immediately disrupted the status quo of the literary and artworlds leading to outcries to ban AI Art and spawning an entirely new market of NFTs Fears over the death of the artist and the death of college composition however are unfounded when considering the historical adoption of emerging technologies by creatives and the reconsideration of authorship that began with poststructuralism and the Foucauldian Death of the Author in 1967